Application of Importance-performance analysis (IPA) in prioritizing the needs of tourism parks stakeholders - Razalli, Mohd Rizal (2015)
The degree of fulfillment of stakeholder needs will greatly affect an organizational performance. Stakeholders are those people that have an interest or concern in an organization.In this case, the stakeholders of the organization are customers of a company that manages tourism parks. Knowing their needs are critical, while prioritizing their needs is even more important to an organization due to scarce available resources. A case study of a tourism park management was carried out to illustrate the importance of prioritizing stakeholders need. Firstly, the current case study attempts to identify the needs of the company’s stakeholders, and secondly will prioritize those needs based on their level of importance.The SERVQUAL and Importance-Performance Analysis (IPA) tools were used for the analysis. Data was gathered through an online survey, which yielded 104 responses.The findings showed that the dimensions of SERVQUAL should be prioritized because of the availability of limited resource. Specifically, Assurance and Empathy were in the quadrant known as the “Keep Up the Good Work”. Responsiveness dimension was found to be in the quadrant of “Concentrate Here” and Reliability was in the quadrant of “Possible Overkill”. Meanwhile the final dimension, Tangibility, was in the quadrant of “Low Priority”. Discussion of the findings is also elaborated in detail.